Persepsi Stakeholder terhadap Corporate Social Responsibility (CSR) PT Bank Jatim Tbk dalam Upaya Pemberdayaan Masyarakat Kota Batu (Journal of Islamic Thought and Philosophy, 2026)
This study analyzes stakeholder perceptions of the implementation of Corporate Social Responsibility (CSR) at PT Bank Jatim Tbk, Batu Branch, within the context of local community empowerment. The research employs a descriptive qualitative approach through in-depth interviews, field observations, and documentation involving internal bank personnel, local government representatives, MSME actors, and beneficiary communities. The findings indicate that CSR is not perceived merely as an assistance program but as a social relationship between a regional financial institution and its community. The social meaning of CSR is shaped by direct experience, repeated interaction, and the relevance of benefits to local needs. Positive perceptions emerge when the program is understood as a development partnership, whereas skepticism arises when activities are viewed as administrative and symbolic. The social legitimacy of the regional bank is determined not by the scale of the program but by relational consistency and institutional proximity to society. The findings also reveal that formal organizational communication has limited influence compared to collective community experience in building trust. Theoretically, the study extends the CSR perspective from an instrumental approach toward a relational approach grounded in stakeholder meaning construction. Practically, the implications highlight the importance of participatory and dialogic approaches in CSR planning so that programs are understood as shared needs rather than external interventions.